2008
DOI: 10.1001/archderm.144.11.1457
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of Patients With Recalcitrant Psoriasis in a Randomized, Observer-Blind, Vehicle-Controlled Trial Using Indigo Naturalis

Abstract: Intervention:The patients applied either indigo naturalis ointment or vehicle ointment topically to each of 2 bilaterally symmetrical psoriatic plaque lesions for 12 weeks (depending on the date of enrollment in the study). Main Outcome Measures:The outcomes were assessed using the following criteria: the sum of ery-thema, scaling, and induration scores and the clearing percentage of the target plaque lesion assessed by 2 blinded observers.Results: Significant reductions in the sum of scaling, erythema, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 10 publications
2
95
1
6
Order By: Relevance
“…We have been developing an alternative approach by topically applying the drug to skin lesions and thousands of psoriasis patients have been treated by this method since 2003 [5]. Results from randomized, observer-blind, vehicle controlled trials of an intra-patient comparison study demonstrated the safe and effective use of topical indigo naturalis ointment for the treatment of chronic plaque psoriasis [23]. The present study, for the first time, demonstrates that indigo naturalis can decrease PCNA expression in both psoriatic lesions and in vitro cultured keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We have been developing an alternative approach by topically applying the drug to skin lesions and thousands of psoriasis patients have been treated by this method since 2003 [5]. Results from randomized, observer-blind, vehicle controlled trials of an intra-patient comparison study demonstrated the safe and effective use of topical indigo naturalis ointment for the treatment of chronic plaque psoriasis [23]. The present study, for the first time, demonstrates that indigo naturalis can decrease PCNA expression in both psoriatic lesions and in vitro cultured keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Malassezia yeasts have been shown to induce the TLR2 pathway (26). However, only to demonstrate the complexity of the participation of Malassezia yeasts in psoriasis pathogenesis, indirubin, a Malassezia-synthesized indole, was successfully employed for the treatment of this disease (200).…”
Section: Psoriasismentioning
confidence: 99%
“…Our previous clinical studies found that topical indigo naturalis ointment was a safe and effective therapy for plaque-type psoriasis [6,7]. We also demonstrated that indigo naturalis and one of its major components, indirubin, could inhibit the cell proliferation of cultured epidermal keratinocytes [8].…”
Section: Introductionmentioning
confidence: 76%